2014
DOI: 10.1039/c4cp03272a
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-breaking in the endofullerene H2O@C60 revealed in the quantum dynamics of ortho and para-water: a neutron scattering investigation

Abstract: a Inelastic neutron scattering (INS) has been employed to investigate the quantum dynamics of water molecules permanently entrapped inside the cages of C 60 fullerene molecules. This study of the supramolecular complex, H 2 O@C 60 , provides the unique opportunity to study isolated water molecules in a highly symmetric environment. Free from strong interactions, the water molecule has a high degree of rotational freedom enabling its nuclear spin isomers, ortho-H 2 O and para-H 2 O to be separately identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
90
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 30 publications
9
90
1
Order By: Relevance
“…INS spectra of water in beryl do not show transitions between the para-and ortho-spin isomer forms of water, which were observed in H 2 O@C 60 endofullerene [12,13], where water also demonstrates absence of HB and rotates almost freely, but did not exhibit evidence of tunneling. The absence of the transitions between the para-and ortho-states in the INS spectra of beryl is probably linked to the fact that water is not as free as in the case of fullerenes (it has a dipole moment perpendicular to the c-axis and it occupies 6-fold equivalent positions across the channel).…”
Section: Q⊥cmentioning
confidence: 99%
See 1 more Smart Citation
“…INS spectra of water in beryl do not show transitions between the para-and ortho-spin isomer forms of water, which were observed in H 2 O@C 60 endofullerene [12,13], where water also demonstrates absence of HB and rotates almost freely, but did not exhibit evidence of tunneling. The absence of the transitions between the para-and ortho-states in the INS spectra of beryl is probably linked to the fact that water is not as free as in the case of fullerenes (it has a dipole moment perpendicular to the c-axis and it occupies 6-fold equivalent positions across the channel).…”
Section: Q⊥cmentioning
confidence: 99%
“…Confined water can be almost free [11], without hydrogen bonds (HB), and display significant quantum behavior. Inelastic neutron scattering (INS) studies have demonstrated that in fullerenes such water exhibits quantum transitions between the para-and ortho-states [12,13], and it has been suggested that quantum tunneling of water explains the fine structure of the optical spectra of beryl [14][15]. INS provides a unique method to study the vibrational and quantum tunneling dynamics of hydrogencontaining materials because of the anomalously large incoherent neutron scattering crosssection of protium (H-1).…”
mentioning
confidence: 99%
“…INS spectrometers and IN1‐Lagrange is a triple‐axis spectrometer equipped with a large area graphite analyser. IN4c and IN1‐Lagrange have been described in earlier papers, IN6 is designed for quasi‐elastic and inelastic neutron scattering. It operates on a cold neutron source and provides good resolution at low energy transfer, accessing both neutron energy (NE) gain and NE loss components of the spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, there is no physical bonding reaction between the encapsulated water molecule and carbon atoms and only nonbonding interaction between them are expected. [8][9][10][11][12][13] With the encapsulation of a single water molecule inside, fundamental properties of C 60 dramatically change, and even show completely novel and unique properties. [14][15][16][17] For example, Insulated by the outer spherical carbon shell, the encapsulated single water molecule shows an enhanced self-diffusion coefficient in comparison with that in bulk water.…”
Section: Introductionmentioning
confidence: 99%